Sequencing of the complete chloroplast genome of Rubia yunnanensis Diels and its phylogenetic analysis. Issue 6 (3rd June 2022) - Wang, Wei; Xu, Tao; Song, Xiangwen; Chen, Cunwu; Liu, Dong; Han, Bangxing; Yi, Shanyong
Abstract: Rubia yunnanensis Diels, an important medicinal herb, is mainly distributed in Yunnan province, Southwest China. In this study, the complete chloroplast genome of R. yunnanensis was successfully sequenced. The assembled chloroplast genome was 155, 108 bp in length with an overall GC content of 36.98%, including a pair of inverted repeat (IR) regions (26, 573 bp, each), respectively, a large single-copy (LSC) region (84, 848 bp) and a small single-copy (SSC) region (17, 114 bp). The genome contained 131 genes, comprising 85 protein-coding genes, 37 tRNA genes, eight rRNA genes, and one pseudogene. The phylogenetic analysis indicated that R. yunnanensis was closely related to R. cordifolia.